Dengue control in Ribeirão Preto, São Paulo, Brazil A experiência do controle do dengue em Ribeirão Preto, São Paulo, Brasil - Afonso Dinis Costa Passos; Eugênia Maria Silveira Rodrigues; Amaury Lelis Dal-Fabbro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Following an epidemic of type I dengue in late 1990, the municipality of Ribeirão Preto (State of São Paulo, Brazil) assumed direct responsibility for the control of Aedes aegypti larvae. Control activities are presented in this report and are based on popular participation and environmental management. Massive use of the communications media, participation by schoolchildren, constant contact with the population, and integration of various public agencies are the program's priorities. Although the drop in the number of susceptibles may have played a role in the reduction of cases after the initial epidemic, the intense preventive campaign certainly helped quell the disease in the city, since changes were observed in the behavior of the population towards potential breeding sites. The occurrence of new cases in recent years appears to be related to greater circulation of the virus in both the State of São Paulo and Brazil as a whole, indicating the need for control measures at the national and continental level, without which it will be difficult to maintain low transmission rates, even in areas submitted to intense preventive work. Após uma epidemia de dengue tipo I no final de 1990, a cidade de Ribeirão Preto (Estado de São Paulo, Brasil) assumiu as atividades de combate às larvas do Aedes aegypti. Tais atividades, baseadas em participação popular e manejo ambiental, são sintetizadas neste trabalho. Utilização maciça dos meios de comunicação, participação de escolares, contato constante com a população e integração de diferentes órgãos públicos são atividades priorizadas pelo programa. Embora a redução de susceptíveis possa ter contribuído para o decréscimo de casos nos anos após a epidemia, o intenso trabalho profilático deve ter exercido papel relevante no controle do dengue na cidade, uma vez que mudanças têm sido observadas em relação ao cuidado com criadouros potenciais. O ressurgimento de casos em anos recentes parece ser devido à maior circulação do vírus no Estado e no País. Tal fato aponta para a necessidade de medidas de controle em nível nacional e continental, sem o que torna-se difícil a manutenção de níveis reduzidos de transmissão, mesmo em áreas intensamente trabalhadas